Understanding The Relation Between Antenatal Care, Vaccination, and Anthropometric Outcomes in Early Childhood: A Cross-Sectional Study - purohit, Isha; Verma, Anjana; purohit, Chelsi; Babu, Raja; Nimawat, Esha; Modi, Kanishk; ashray, guduru satya; deshpande, shruti; Goel, Anika; walia, sanya; choudhary, lokesh; Bagadia, Bhoomi (Pediatric Review: International Journal of Pediatric Research, 2025)
Background: The under-5 mortality rate is a sensitive indicator of a nation’s public health measures. It is influenced by multiple factors, including socioeconomic status, antenatal care, immunization, and education. Maternal care during pregnancy and maternal education play a crucial role in ensuring optimal child health outcomes, with effects that persist into adolescence. Despite various government initiatives in India, gaps in antenatal care utilization and vaccination persist, particularly in rural areas. This study examines the relationship between antenatal care factors, immunization status, and anthropometric outcomes in early childhood. Methods: A cross-sectional study was conducted in rural areas. Data were collected from 100 mothers regarding their demographic details, antenatal care visits, and children’s anthropometric measurements. Chi-square tests were used to analyze associations between demographic variables and anthropometric measures, such as weight-for-age classifications based on the Indian Academy of Pediatrics and WHO growth charts, along with mid-upper arm circumference. Statistical Analysis: SPSS software was used to analyse the data. Chi Square test was used. Results: Significant associations were found between maternal education and weight-for-age classification (p = 0.016, p = 0.015). Additionally, positive correlations were observed between immunization status and anthropometric measures (p = 0.040), while the mode of delivery was also correlated with anthropometric measures (p = 0.042), aligning with previous studies linking delivery type to adolescent lean body mass. The findings highlight the importance of antenatal care in determining early childhood growth patterns. Conclusion: This study underscores the need for improved antenatal care utilization to enhance child growth outcomes. Identifying factors contributing to the underutilization of antenatal care in rural areas is essential for ensuring a continuum of care. Strengthening maternal healthcare services can lead to better anthropometric outcomes and reduced child mortality.